The Use of Creative and Productive Models Assisted by Picture Media to Improve the Skills of Writing Descriptive Text in Grade VII Students of SMN 2 Sungguminasa - Hanana Muliana; Muhammad Dahlan; Lisda Frediningsih (Universitas Muhammadiyah Enrekang, 2024)
Improving Descriptive Text Writing Skills Using Creative and Productive Models Through Image Media for Grade VII Students of SMPN 2 Sungguminasa. This study aims to improve the learning outcomes of grade VII students of SMPN 2 Sungguminasa in learning to write descriptive texts using creative and productive models through image media in the 2022-2023 academic year. Data collection was carried out using text and non-test techniques, in the form of observation, documentation, and products. Data analysis techniques consist of quantitative and qualitative data. This study uses Classroom Action Research (CAR). The subjects of this study were 30 students in grade VII consisting of 13 male students and 17 female students. In this study, two cycles were carried out, each cycle consisting of cycle I meeting 1, and cycle II with 1 meeting. This study only focuses on one class. Based on the results of the data analysis, it is known that after the creative and productive model through image media was applied, students' descriptive text writing skills increased. This can be seen from the increase in the completion of student learning outcomes in cycle I of 44.83 and cycle II of 86.50, the difference between cycle I and cycle II of 41.67%. experienced an increase. From the data analysis, it can be understood that the learning outcomes of grade VII students of SMPN 2 Sungguminasa in learning to write descriptive texts using creative and productive models through image media can improve students' writing skills in the Indonesian Language subject.